2015
DOI: 10.1021/cs501585k
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Bulk-Composition-Dependent H2 Adsorption Energies on CuxPd1–x Alloy (111) Surfaces

Abstract: The bulk-composition-dependent dissociative adsorption energy of hydrogen on CuPd alloys has been measured experimentally and modeled using density functional theory. The hydrogen adsorption energy cannot be simply defined by a single reactive site or as a composition weighted average of the pure metal components. We developed a modeling approach that uses a basis of active sites weighted by a model site probability distribution to estimate a bulk-composition-dependent adsorption energy. The approach includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…The microreactor was used in two recent studies that examined the reactivity of a Cu x Pd 1– x CSAF for H 2 ‐D 2 exchange . In that work, the conversion of H 2 to HD was measured at 100 locations on the CSAF as a function of temperature (300–600 K).…”
Section: Composition Alloy Spread Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microreactor was used in two recent studies that examined the reactivity of a Cu x Pd 1– x CSAF for H 2 ‐D 2 exchange . In that work, the conversion of H 2 to HD was measured at 100 locations on the CSAF as a function of temperature (300–600 K).…”
Section: Composition Alloy Spread Filmsmentioning
confidence: 99%
“…Above x Pd = 0.40, however, this trend ceased, with adsorption barriers becoming independent of Pd composition. To investigate this phenomenon, we developed a novel approach to modeling composition spread alloy surfaces using density functional theory . We found that the region of near linear decrease in adsorption barriers with lower values than suggested by linear interpolation of the pure component values, x Pd < 0.40 were readily explained by hydrogen‐induced segregation of Pd to the surface.…”
Section: Composition Alloy Spread Filmsmentioning
confidence: 99%
“…We will provide an example of this for a paper we recently published in ACS Catalysis on "Estimating Bulk-Composition-Dependent H 2 Adsorption Energies on Cu x Pd 1−x Alloy (111) Surfaces". 11 The Supporting Information file for that article is available for free. 12 When opened in a PDF reader that supports attachments, one can see that there are attachments (see Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…11 The Supporting Information file for that article is available for free. 12 When opened in a PDF reader that supports attachments, one can see that there are attachments (see Figure 1 a). Alternatively, while reading the PDF file, the reader is alerted that there is an attachment by the presence of a thumbtack icon (Figure 1 b), which can be double clicked to open the file.…”
Section: Introductionmentioning
confidence: 99%
“…Through scripting, one could recreate the actual The key point here is that the data was read by a computer from the 146 supporting information file, and then reused to create a new figure. We 147 have used this approach to embed both computational and experimen-148 tal temperature programmed desorption data in supporting informa-149 tion [25], and experimental reactivity and segregation data [30,31].…”
mentioning
confidence: 99%